2017
DOI: 10.1007/s11739-017-1691-z
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life impairment in Behçet’s disease and relationship with disease activity: a prospective study

Abstract: Our aim was to prospectively investigate the impact of Behçet's disease (BD), disease activity, and clinical and demographic characteristics on different aspects of quality of life (QoL) measured by the short-form (SF)-36 QoL scale. We administered the SF-36 to 37 consecutive BD patients in different moments of disease activity, and to 23 healthy controls (HC). The eight subcategories of the SF-36 underwent statistical analysis for identifying differences and correlations. Compared to HC, BD patients showed si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 28 publications
3
22
1
1
Order By: Relevance
“…Because of all these factors, one could say that people with a higher level of education might have higher QoL (Canpolat and Yurtsever, 2011). Similar indings were reported by a recent study which showed that BD patients had signi icantly lower mean scores in all the SF-36 QoL subscores except for mental health and role-emotional for which the results was not signi icantly lower (Fabiani et al, 2017).…”
Section: Resultssupporting
confidence: 82%
“…Because of all these factors, one could say that people with a higher level of education might have higher QoL (Canpolat and Yurtsever, 2011). Similar indings were reported by a recent study which showed that BD patients had signi icantly lower mean scores in all the SF-36 QoL subscores except for mental health and role-emotional for which the results was not signi icantly lower (Fabiani et al, 2017).…”
Section: Resultssupporting
confidence: 82%
“…In some cases, eye involvement leads to loss of vision. Therefore, patients with eye involvement are markedly limited in their daily life activities, and their QOL is decreased [12,17,18]. Based on the SF-36, Fabiani et al reported that the physical functioning score was significantly worse in patients with BD with eye disease than in patients with BD without ocular involvement [16].…”
Section: Discussionmentioning
confidence: 99%
“…", Mumcu and colleagues investigated the patient's perspective in subjects affected by BS and psoriasis through a specific questionnaire [36]. According to previous findings, fatigue and pain were frequently reported by BS patients, impairing the quality of life [37]. In the study of this topical collection, musculoskeletal and eye involvements highlighted the negative beliefs about the illness, while the worst score on psychological attribution was reported by psoriatic patients [36].…”
Section: Clinical Manifestations and Phenotypesmentioning
confidence: 99%